Incorporating Social Networks in Business Relationships of Retail SMEs for Better Business Performance - Asmahani Ibrahim, Nor; Mohd Roslin, Rosmimah (International Journal of Engineering and Technology, 2018)
The presence of hypermarkets with modern retail format has impacted the performance of retail small medium-enterprises (SMEs) in Malaysia. The challenges of remaining competitive and the ability to sustain the business have pushed many retail SMEs to cease operations within a short period after commencement. Despite these challenges, retail SMEs can still attain competitive advantage through the strategies of strengthening and maintaining business relationships with their social networks. This study postulates that fostering social networks, specifically on the notion of homophily or similarities among social network members, is able to lure valuable resources needed by retail SMEs in achieving superior business performance. Unfortunately, only few studies have focused on social networks from within the Asian context and many tend to overlook the importance of social networks specifically in retailing. This study also suggests the relationship between value and status similarities of retail SMEs and their ability to coordinate efforts in horizontal relationships. Therefore, this study extends the discussion on the role of social networks towards better business performance of retail SMEs in Malaysia by conceptualizing a framework indicating the importance of value and status homophily on coordination of activities leading to business performance of retail SMEs.
Keywords: social networks; retail SMEs; coordination; business performance